2017
DOI: 10.1016/j.jvs.2016.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of postcarotid endarterectomy hypertension after eversion versus conventional carotid endarterectomy

Abstract: E-CEA increases the risk for post-CEA hypertension, whereas C-CEA is more often associated with hypotension, Careful BP monitoring at least in the early postoperative period after CEA is mandatory, especially when the eversion technique is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…In 1924, Hering discovered that these baroreceptors were located in the CS. 5,[11][12][13] The CS is a dilatation in the carotid bifurcation usually at the origin of the proximal ICA. The most common site is the origin of the ICA, in 74.3%, but the CS can also be found in the distal part of the CCA inferior to the bifurcation and it contains baroreceptors that influence BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1924, Hering discovered that these baroreceptors were located in the CS. 5,[11][12][13] The CS is a dilatation in the carotid bifurcation usually at the origin of the proximal ICA. The most common site is the origin of the ICA, in 74.3%, but the CS can also be found in the distal part of the CCA inferior to the bifurcation and it contains baroreceptors that influence BP.…”
Section: Discussionmentioning
confidence: 99%
“…These evidenced post-ECEA high levels of the arterial blood pressure (BP) have been associated with multiple and severe complications and the phenomenon is attributed to the poor functionality of the baroreceptor mechanism. 5 The transection of the baroreceptor sensoring tissue leads to the interruption of the negative feedback reflex. The main mass of the baroreceptor tissue is located in the carotid body's adventitia and media, with the primary location at the medial part of the ICA stem, and these receptors consist the terminal points of the abducting fibers which through the Hering nerve run to the glossopharyngeal nerve.…”
mentioning
confidence: 99%
“…However, eversion CEA has a signifi cantly lower rate of late stenosis [64,65]. By meta-analysis, Demirel et al [66] found moderate evidence for an increased rate of post-CEA hypertension (OR 2.8) with eversion CEA.…”
Section: Benefi T and Harm From Treatmentmentioning
confidence: 99%
“…However, eCEA is limited by an inability to insert a shunt until the plaque has been removed and by a significantly higher incidence of post-CEA hypertension. 1 On the other hand, dCEA is associated with higher rates of perioperative stroke, peri-operative thrombosis and higher rates of late restenosis and late ipsilateral stroke compared with routine pCEA, 2,3 while pCEA is vulnerable to late prosthetic patch infection in about 1% of patients. 4 Several randomised controlled trials (RCTs) and observational studies (OSs) have compared eCEA with cCEA with regard to short-term outcomes (30 day stroke, 30 day death/stroke, 30 day death/stroke/myocardial infarction [MI], cranial nerve injury [CNI], neck haematoma, and 30 day internal carotid artery [ICA] thrombosis) as well as late outcomes (late restenosis, late ipsilateral stroke).…”
Section: Introductionmentioning
confidence: 99%